2009
DOI: 10.1161/hypertensionaha.109.134049
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Differences by Ethnic Group Among United States Children and Adolescents

Abstract: Large differences in blood pressure by ethnic group are apparent among adults. There is uncertainty as to whether similar differences by ethnic group exist among children and if so, the age of onset. Blood pressure (BP) measurements were obtained from 58,698 children at 78,556 visits using data from the Pediatric Task Force data, a collection of 11 studies with BP data from children and adolescents age 1–17. Generalized estimating equation methods were used to identify sex-specific differences in body mass ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
2
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 22 publications
5
47
2
8
Order By: Relevance
“…This suggests that at some point, the obesity effect on BP may overshadow the race effect on BP. Consistent with our data, the Pediatric Task Force also shows BMI-adjusted differences in rates of BP elevation in Hispanic versus white boys (15).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This suggests that at some point, the obesity effect on BP may overshadow the race effect on BP. Consistent with our data, the Pediatric Task Force also shows BMI-adjusted differences in rates of BP elevation in Hispanic versus white boys (15).…”
Section: Discussionsupporting
confidence: 91%
“…The same study also found white children with the highest BMIs had more hypertension than black children with equivalent BMIs (28). The Pediatric Task Force shows black-white race differences in BMI-adjusted rates of BP elevation in normal weight populations only (15). This suggests that at some point, the obesity effect on BP may overshadow the race effect on BP.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A recent study, however, showed a higher prevalence of elevated BP among Black compared with White American boys aged Ͻ18 years even after controlling for BMI. 26 A US-United Kingdom comparison of children of African origin is complicated by the differences in migration history, with Africans in the United Kingdom being much more likely to be migrants or born to migrant parents than Black Americans in the United States. The history of Black Caribbeans reflects longer generational distance from West Africa than that of Africans in the United Kingdom but less than that of Black Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Significant prevalence rates of prehypertension and hypertension have been reported in adolescents. 7 Rosner et al 8 completed a pooled analysis of children and adolescents Յ17 years of age and found hypertension in 6% and prehypertension in another 15% of the study population. The racial disparities in prevalence rates found in adult blood pressures were also evident in this younger group.…”
mentioning
confidence: 99%